FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI BAWANG MERAH DI DESA NGEPOH KECAMATAN DRINGU KABUPATEN PROBOLINGGO - Irfan Arif Firmansyah; Ebban Bagus Kuntadi (UPT Penerbitan Universitas Jember, 2018)
The study aimed to determine factors that affected the income of red onion farming in Ngepoh Village, Dringu Subdistrict, Probolinggo Regency. The method in determining the research area was purposively conducted. with the consideration that the Ngepoh Village is one of the potential areas where the majority of the population make a living as farmers who cultivated red onion and the area was also one of the red onion production centers in Dringu Subdistrict. The research method used were analytical and descriptive. The sampling method used in this study was the proportionate stratified random sampling method because farmers in Ngepoh Village possesed different land area characteristics. The number of samples used was obtained based on the use of the Slovin formula with an error rate of 15%. Data collection method was done by interview, observation, and documentation. Data analysis was performed with multiple linear regression analysis. The results of the study showed that factors that significantly affected the income of red onion were cost of seeds,